PUR protective hose and preparation method thereof
By using PUR protection hoses prepared with raw materials such as PUR resin, the existing wiring harness protection hoses have solved the problems of installation stability, cost, temperature resistance, flexibility and matte powder precipitation, and achieved excellent mechanical properties, wear resistance and chemical stability.
Patent Information
- Application Number
- CN202411893497.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-18
AI Technical Summary
The existing wiring harness protection hoses have problems such as unstable installation, high cost, poor temperature resistance, insufficient flexibility, and easy precipitation of matte powder, which affects appearance and service life.
PUR protection hose is prepared by extrusion molding process by using raw materials such as PUR resin, SBS elastomer, maleic anhydride grafted SBS copolymer, itaconic acid grafted SBS copolymer, PUR coated inorganic filler masterbatch, lubricant and antioxidant.
It achieves excellent mechanical properties, wear resistance and chemical stability of the hose, enhances flexibility and rebound properties, improves impact resistance and service life, and solves the problems of easy slippage and precipitation of frosted powder in traditional hoses.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PUR protective sleeves, and in particular relates to a PUR protective hose and a preparation method thereof. Background Art
[0002] With the optimization of automobile structural design, in order to make full use of the space inside the car, some wiring harnesses are usually arranged at the bottom of the car. These wiring harnesses may come into contact with the ground during driving, which may easily cause wear. At the same time, splashing water droplets, mud and dust may cause corrosion or pollution to the wiring harnesses, further increasing safety hazards.
[0003] At present, commonly used harness protection hoses include PUR smooth hoses, PVC hoses and PA / PP corrugated hoses. However, these hoses have defects to varying degrees in actual use. PUR smooth hoses are too smooth on the surface, which makes them difficult to fix during installation and easy to slip off. In addition, in order to improve hydrolysis resistance, polyether PUR materials are required, but the cost of this material is relatively high. PA / PP corrugated hoses are relatively hard and have poor flexibility, which makes them unsuitable for complex wiring environments. Although PVC hoses are relatively low in cost, they have poor temperature resistance and are difficult to meet the requirements of the bottom environment of the car.
[0004] In order to improve the performance of the harness protection hose, some products add frosting powder to the material to increase the friction of the surface. However, in the existing technology, adding a small amount of frosting powder fails to significantly improve the anti-slip performance or enhance the friction effect. However, when the amount added is too much, the frosting powder may precipitate, affecting the appearance and service life; at the same time, excessive frosting powder may reduce the flexibility and tensile strength of the pipe, and have an adverse effect on the mechanical properties. Summary of the invention
[0005] The purpose of the present invention is to solve the above-mentioned shortcomings and provide a PUR protective hose and a preparation method thereof.
[0006] In the first aspect, a PUR protective hose adopts the following technical solution:
[0007] A PUR protective hose comprises raw materials, measured in parts by weight, including: 40-80 parts of PUR resin, 5-15 parts of SBS elastomer, 5-10 parts of maleic anhydride grafted SBS copolymer, 1-5 parts of itaconic acid grafted SBS copolymer, 5-10 parts of PUR coated inorganic filler masterbatch, 1-3 parts of lubricant and 0.5-1 part of antioxidant.
[0008] Furthermore, the PUR resin includes one or more of polyester resin and polyether resin; the hardness of the PUR resin is 75A to 90A;
[0009] The inorganic filler includes one or more of white carbon black, glass fiber, light calcium carbonate, heavy calcium carbonate, talc, mica, kaolin, silicon dioxide, titanium dioxide, red mud, fly ash, diatomaceous earth, wollastonite, glass microspheres, barium sulfate and calcium sulfate;
[0010] The lubricant includes one or more of paraffin, polyethylene wax, stearic acid, hydroxystearic acid, vinyl bisstearamide, butyl stearate, oleamide, barium stearate, zinc stearate, calcium stearate, cadmium stearate, magnesium stearate, lead stearate, and silicone oil;
[0011] The antioxidant includes one or more of a hindered phenol antioxidant, a phosphite antioxidant and a hindered amine antioxidant.
[0012] Furthermore, the raw materials also include 15 to 20 parts of flame retardant and 1 to 5 parts of masterbatch in parts by weight.
[0013] Furthermore, the flame retardant includes one or more of halogen flame retardant, phosphorus flame retardant, nitrogen flame retardant, phosphorus nitrogen flame retardant, and inorganic hydroxide; and the masterbatch includes a masterbatch with a PUR carrier.
[0014] In the second aspect, a method for preparing a PUR protective hose adopts the following technical solution:
[0015] A preparation method of a PUR protective hose comprises the following steps: PUR resin, SBS elastomer, maleic anhydride grafted SBS copolymer, itaconic acid grafted SBS copolymer, PUR coated inorganic filler masterbatch, lubricant, antioxidant, flame retardant and masterbatch raw materials are uniformly mixed according to weight parts, and then extruded into a tube to obtain the PUR protective hose.
[0016] Furthermore, the preparation method of the maleic anhydride grafted SBS copolymer comprises the following process: dissolving SBS elastomer in an organic solvent and copolymerizing with maleic anhydride monomer under the action of an initiator, and precipitating and filtering to obtain the maleic anhydride grafted SBS copolymer.
[0017] Furthermore, the preparation method of the maleic anhydride grafted SBS copolymer comprises the following steps:
[0018] The SBS elastomer is dissolved in xylene, maleic anhydride monomer and initiator BPO are added, and the temperature is raised to 100° C. to 110° C. in an inert atmosphere for reaction for 3 h to 5 h, and anhydrous ethanol is added for precipitation, filtered, washed, and dried to obtain the maleic anhydride grafted SBS copolymer.
[0019] Furthermore, the preparation method of the itaconic acid grafted SBS copolymer comprises the following process: dissolving SBS elastomer in an organic solvent and copolymerizing itaconic acid monomer under the action of an initiator, and precipitating and filtering to obtain the maleic anhydride grafted SBS copolymer.
[0020] Furthermore, the preparation method of the itaconic acid grafted SBS copolymer comprises the following process:
[0021] The SBS elastomer is dissolved in xylene, and itaconic acid monomer and initiator BPO are added. In an inert atmosphere, the temperature is raised to 100° C. to 110° C. for reaction for 3 h to 5 h. Acetone is added for precipitation, and the mixture is filtered, washed, and dried to obtain the itaconic acid grafted SBS copolymer.
[0022] Furthermore, the PUR coated inorganic filler masterbatch is prepared by dispersing an inorganic filler and an isocyanate in an organic solvent, dropping a polyether polyol solution, adding a crosslinking agent after heating, and performing a crosslinking reaction under the action of a catalyst;
[0023] The preparation method of the PUR-coated inorganic filler masterbatch comprises the following steps:
[0024] The inorganic filler and isocyanate MDI are dissolved in xylene and fully dispersed under an inert atmosphere, and then a mixed solution of polyether polyol and xylene is added dropwise, the temperature is raised to 70° C. to 80° C., and a crosslinking agent pentaerythritol and a catalyst dibutyltin dilaurate are added to carry out a crosslinking reaction for 2 h to 2.5 h. After filtering, washing, drying and grinding, the PUR-coated inorganic filler masterbatch is obtained.
[0025] Beneficial effects of the present invention:
[0026] The present invention provides a PUR protective hose, in which PUR resin is used as a main substrate, and the hose provides excellent mechanical properties, wear resistance and chemical stability. The optimization of the dosage range ensures the balance between toughness and strength of the material, and is adaptable to various complex working conditions. The introduction of SBS elastomer enhances the flexibility and resilience of the hose, so that it can maintain good deformation resistance in narrow and dynamic environments such as the bottom of a car, and further improves the impact resistance and service life of the hose. The synergistic effect of maleic anhydride grafted SBS copolymer and itaconic anhydride grafted SBS copolymer significantly improves the compatibility with the PUR substrate by introducing polar groups into the SBS molecular structure, and at the same time gives the material higher chemical stability and processing performance, which not only effectively improves the strength and hydrolysis resistance of the hose, but also enhances its reliability in use under high temperature and humid heat environments. By introducing PUR-coated inorganic filler masterbatch as the core of the cross-linked particles, a matte and frosted appearance is formed on the surface of the protective hose, which not only solves the technical problem of easy precipitation and uneven dispersion of traditional inorganic fillers in the substrate, but also significantly enhances the friction between the outer walls of the protective hose, preventing the technical problem of easy slippage of the protective hose during installation; the reasonable addition of lubricant not only reduces the friction resistance during processing and ensures the processing fluidity of the material, but also forms a thin lubricating layer in the finished product, which helps to improve the scratch resistance and feel of the hose surface; the addition of antioxidants effectively delays the oxidative degradation of the material during processing and use, and enhances the thermal oxygen stability and long-term performance of the hose. DETAILED DESCRIPTION
[0027] The following is a further detailed description of a PUR protective hose and a preparation method thereof described in the present invention in conjunction with the examples. For the sake of simplicity of description, this document cannot list all the alternative technical features and implementation schemes included in the present invention. Therefore, those skilled in the art should be aware that any technical features and implementation schemes in this embodiment do not limit the scope of protection of the present invention, which includes any alternative technical features and implementation schemes adopted by all those skilled in the art without creative labor. Specifically, implementation schemes obtained by replacing any technical feature in the present invention or combining any two or more technical features provided by the present invention should be within the scope of protection of the present invention.
[0028] The present embodiment provides a PUR protective hose, and the raw materials, measured in parts by weight, include: 40 to 80 parts of PUR resin, 5 to 15 parts of SBS elastomer, 5 to 10 parts of maleic anhydride grafted SBS copolymer, 1 to 5 parts of itaconic acid grafted SBS copolymer, 5 to 10 parts of PUR coated inorganic filler masterbatch, 1 to 3 parts of lubricant and 0.5 to 1 part of antioxidant.
[0029] In some embodiments, the PUR resin includes one or more of a polyester resin and a polyether resin; the hardness of the PUR resin is 75A to 90A;
[0030] The inorganic filler includes one or more of white carbon black, glass fiber, light calcium carbonate, heavy calcium carbonate, talc, mica, kaolin, silicon dioxide, titanium dioxide, red mud, fly ash, diatomaceous earth, wollastonite, glass microspheres, barium sulfate and calcium sulfate;
[0031] The lubricant includes one or more of paraffin wax, polyethylene wax, stearic acid, hydroxystearic acid, vinyl bisstearamide, butyl stearate, oleamide, barium stearate, zinc stearate, calcium stearate, cadmium stearate, magnesium stearate, lead stearate, and silicone oil;
[0032] The antioxidant includes one or more of a hindered phenol antioxidant, a phosphite antioxidant and a hindered amine antioxidant.
[0033] In some embodiments, the raw materials further include 15 to 20 parts of flame retardant and 1 to 5 parts of masterbatch in parts by weight.
[0034] In some embodiments, the flame retardant includes one or more of halogen flame retardant, phosphorus flame retardant, nitrogen flame retardant, phosphorus nitrogen flame retardant, and inorganic hydroxide; the masterbatch includes a masterbatch with a PUR carrier.
[0035] The present embodiment provides a method for preparing a PUR protective hose, comprising the following process: mixing PUR resin, SBS elastomer, maleic anhydride grafted SBS copolymer, itaconic acid grafted SBS copolymer, PUR coated inorganic filler masterbatch, lubricant, antioxidant, flame retardant and masterbatch raw materials in parts by weight and then extruding and forming the mixture to obtain a PUR protective hose.
[0036] In some embodiments, the preparation method of the maleic anhydride grafted SBS copolymer includes the following process: dissolving the SBS elastomer in an organic solvent and copolymerizing it with the maleic anhydride monomer under the action of an initiator, and then precipitating and filtering to obtain the maleic anhydride grafted SBS copolymer.
[0037] In some embodiments, the method for preparing the maleic anhydride grafted SBS copolymer comprises the following steps:
[0038] The SBS elastomer is dissolved in xylene, maleic anhydride monomer and initiator BPO are added, and the temperature is raised to 100°C to 110°C in an inert atmosphere for reaction for 3h to 5h, anhydrous ethanol is added for precipitation, and the mixture is filtered, washed, and dried to obtain a maleic anhydride grafted SBS copolymer.
[0039] The preparation method of maleic anhydride grafted SBS copolymer chemically bonds the polar groups of maleic anhydride to the SBS molecular chain through a free radical grafting reaction, thereby significantly improving the polarity of SBS and its compatibility with the polar PUR substrate. Specifically, the method uses xylene as a solvent to completely dissolve the SBS elastomer to form a uniform reaction system, and at the same time provides a suitable thermodynamic environment for the grafting reaction by heating. Under an inert atmosphere (such as nitrogen protection), maleic anhydride monomer and free radical initiator BPO are added. The initiator generates free radicals by decomposition, inducing a free radical grafting reaction between maleic anhydride and the SBS main chain to form a grafted copolymer. By precisely controlling the reaction conditions, the grafting efficiency is effectively improved, and the uniformity and chemical stability of the copolymer are ensured.
[0040] After the reaction is completed, anhydrous ethanol is added to the system for precipitation, and the maleic anhydride grafted SBS copolymer is precipitated from the solution, while the unreacted maleic anhydride and other low molecular weight byproducts are effectively removed by the solvent. After vacuum filtration and multiple washings, the purity of the product is further improved. Finally, by drying at a controlled temperature, a maleic anhydride grafted SBS copolymer with good stability is obtained.
[0041] This method significantly enhances the interfacial bonding between SBS and PUR polar materials by introducing reactive maleic anhydride groups into SBS molecules, improves its dispersibility and compatibility in composite materials, and gives the composite materials higher mechanical strength, chemical resistance and environmental stability.
[0042] In some embodiments, the method for preparing itaconic acid grafted SBS copolymer includes the following process: dissolving SBS elastomer in an organic solvent and copolymerizing itaconic acid monomer under the action of an initiator, and precipitating and filtering to obtain a maleic anhydride grafted SBS copolymer.
[0043] In some embodiments, the method for preparing itaconic acid grafted SBS copolymer comprises the following steps:
[0044] The SBS elastomer is dissolved in xylene, and itaconic acid monomer and initiator BPO are added. In an inert atmosphere, the temperature is raised to 100°C to 110°C for reaction for 3h to 5h. Acetone is added for precipitation, and the mixture is filtered, washed, and dried to obtain an itaconic acid grafted SBS copolymer.
[0045] The preparation method of itaconic acid grafted SBS copolymer chemically bonds the polar groups of itaconic acid to the SBS molecular chain through a free radical grafting reaction, thereby significantly enhancing the polarity of SBS and the interfacial compatibility with the PUR polar substrate. First, the SBS elastomer is dissolved in xylene to form a stable and uniform solution system to ensure the smooth progress of subsequent reactions. Under an inert atmosphere (such as nitrogen protection), itaconic acid monomer and free radical initiator BPO are added. The initiator generates free radicals by thermal decomposition, inducing a grafting reaction between itaconic acid and SBS to form a grafted copolymer containing active polar groups.
[0046] By precisely controlling the reaction conditions, the reaction can generate stable itaconic acid grafted SBS copolymers with high efficiency while effectively avoiding the occurrence of side reactions. After the reaction is completed, the grafted copolymer is precipitated from the reaction solution by adding acetone, effectively removing unreacted itaconic acid monomers and other low-molecular byproducts. Subsequently, vacuum filtration and multiple washing steps are performed to further ensure the high purity of the product. Finally, by drying at an appropriate temperature, an itaconic acid grafted SBS copolymer with excellent chemical stability and structural integrity is obtained.
[0047] By introducing active polar groups, itaconic acid grafted SBS copolymer significantly improves its compatibility and interfacial bonding with polar substrates such as PUR, while giving the composite material higher chemical resistance and environmental stability.
[0048] In some embodiments, the PUR coated inorganic filler masterbatch is prepared by dispersing an inorganic filler and an isocyanate in an organic solvent, dropping a polyether polyol solution, adding a crosslinking agent after heating, and performing a crosslinking reaction under the action of a catalyst;
[0049] The preparation method of PUR coated inorganic filler masterbatch includes the following processes:
[0050] The inorganic filler and isocyanate MDI are dissolved in xylene and fully dispersed under an inert atmosphere, and then a mixed solution of polyether polyol and xylene is added dropwise, the temperature is raised to 70°C to 80°C, and cross-linking agent pentaerythritol and catalyst dibutyltin dilaurate are added to carry out a cross-linking reaction for 2h to 2.5h. After filtering, washing, drying and grinding, PUR-coated inorganic filler masterbatch is obtained.
[0051] The preparation method of PUR coated inorganic filler masterbatch forms a uniform PUR elastomer coating layer on the surface of the inorganic filler through a chemical crosslinking reaction, thereby significantly improving the compatibility and dispersion performance of the inorganic filler and the polymer substrate. Specifically, the inorganic filler and the isocyanate MDI are dispersed in xylene, and an inert atmosphere (such as nitrogen protection) is used to avoid oxidation or side reactions during the reaction. Subsequently, a polyether polyol solution is added dropwise, and the isocyanate and the polyol undergo an addition reaction to form a polyurethane precursor, which provides a basis for further crosslinking.
[0052] After the temperature is raised to 70℃~80℃, the crosslinking agent pentaerythritol and the catalyst dibutyltin dilaurate are added to start the crosslinking reaction, which prompts the polyurethane molecules to form a three-dimensional network structure on the filler surface. This crosslinking process not only improves the mechanical strength and stability of the filler surface, but also improves its dispersibility and bonding force in the polyurethane matrix. Finally, through post-processing steps such as filtration, washing, drying and grinding, the unreacted products and solvents are removed to obtain a PUR-coated inorganic filler masterbatch with high purity and excellent performance.
[0053] This preparation method introduces a PUR coating layer on the surface of the inorganic filler, which not only effectively avoids the precipitation of the filler during use, but also significantly improves the wear resistance, dimensional stability and mechanical strength of the composite material.
[0054] Example
[0055] Example 1
[0056] Example 1 provides a PUR protective hose, the raw materials including: 40kg of PUR resin, 5kg of SBS elastomer, 5kg of maleic anhydride grafted SBS copolymer, 1kg of itaconic acid grafted SBS copolymer, 5kg of PUR coated talc masterbatch, 1kg of calcium stearate and 0.5kg of antioxidant; wherein the antioxidant is a compound antioxidant of 1076 and 1010 type antioxidants in a mass ratio of 1:1.
[0057] Embodiment 1 provides a method for preparing a PUR protective hose, comprising the following steps: mixing the raw materials uniformly by weight and then extruding the raw materials into a tube to obtain a PUR protective hose.
[0058] Example 1 also provides a method for preparing a maleic anhydride grafted SBS copolymer, comprising the following steps:
[0059] SBS and xylene were placed in a four-necked flask and heated to 100°C. After SBS was completely dissolved, the grafted monomer MAH and the initiator BPO were added, nitrogen was introduced for protection, and the reaction was carried out at 100°C for 5 hours. Then, anhydrous ethanol as a precipitant was added to the system while stirring at a high speed. The product was separated by vacuum filtration and repeatedly washed with the precipitant. Finally, it was vacuum dried at 80°C to obtain a maleic anhydride grafted SBS copolymer.
[0060] Example 1 also provides a method for preparing an itaconic acid grafted SBS copolymer, comprising the following steps:
[0061] SBS and xylene were placed in a four-necked flask and heated to 100°C. After SBS was completely dissolved, the grafting monomer ITA and initiator BPO dissolved in n-butanol were added, nitrogen was introduced for protection, and the reaction was carried out at 100°C for 5 hours. Then, the precipitant acetone was added to the system while stirring at high speed. The product was separated by vacuum filtration and repeatedly washed with the precipitant. Finally, it was vacuum dried at 80°C to obtain the itaconic acid grafted SBS copolymer.
[0062] Example 1 also provides a method for preparing a PUR-coated talc masterbatch, comprising the following steps:
[0063] 1000g of talc was dried in an oven at 100℃ for 6h, placed in a 5L four-necked flask, 30g of MDI and 2000mL of xylene were added, nitrogen was introduced to remove the air in the flask, the temperature was raised to 40℃, ultrasonic dispersion was performed for 30min while stirring fully, and then a mixed solution of 70g of polyether polyol N220 and 100mL of xylene was added dropwise to the three-necked flask, and the addition was completed within half an hour. Then the temperature was raised to 75℃, 8g of pentaerythritol and 2g of dibutyltin dilaurate were added for cross-linking reaction, and after reacting for 2h, the mixture was filtered, washed, dried and ground in sequence to obtain PUR coated talc masterbatch.
[0064] Example 2
[0065] Example 2 provides a PUR protective hose, the raw materials including: 80kg of PUR resin, 15kg of SBS elastomer, 10kg of maleic anhydride grafted SBS copolymer, 10kg of itaconic acid grafted SBS copolymer, 10kg of PUR coated talc masterbatch, 3kg of calcium stearate and 1kg of antioxidant; wherein the antioxidant is a compound antioxidant of 1076 and 1010 type antioxidants in a mass ratio of 1:1.
[0066] Embodiment 2 provides a method for preparing a PUR protective hose, comprising the following steps: the raw materials are mixed uniformly by weight and then extruded into a tube to obtain a PUR protective hose.
[0067] Example 2 also provides a method for preparing a maleic anhydride grafted SBS copolymer, comprising the following steps:
[0068] SBS and xylene were placed in a four-necked flask and heated to 110°C. After SBS was completely dissolved, the grafted monomer MAH and the initiator BPO were added, and nitrogen was introduced for protection. The reaction was carried out at 110°C for 3 hours. Then, anhydrous ethanol as a precipitant was added to the system while stirring at a high speed. The product was separated by vacuum filtration and repeatedly washed with a precipitant. Finally, it was vacuum dried at 90°C to obtain a maleic anhydride grafted SBS copolymer.
[0069] Example 2 also provides a method for preparing an itaconic acid grafted SBS copolymer, comprising the following steps:
[0070] SBS and xylene were placed in a four-necked flask and heated to 110°C. After SBS was completely dissolved, the grafting monomer ITA and initiator BPO dissolved in n-butanol were added, nitrogen was introduced for protection, and the reaction was carried out at 110°C for 3 hours. Then, the precipitant acetone was added to the system while stirring at a high speed. The product was separated by vacuum filtration and repeatedly washed with the precipitant. Finally, it was vacuum dried at 80°C to obtain the itaconic acid grafted SBS copolymer.
[0071] Embodiment 2 also provides a method for preparing a PUR-coated talc masterbatch, comprising the following steps:
[0072] 1000g of talcum powder was dried in an oven at 120℃ for 8h, placed in a 5L four-necked flask, 30g of MDI and 2000mL of xylene were added, nitrogen was introduced to remove the air in the flask, the temperature was raised to 40℃, ultrasonic dispersion was performed for 30min while stirring fully, and then a mixed solution of 70g of polyether polyol N220 and 100mL of xylene was added dropwise to the three-necked flask, and the addition was completed within half an hour. Then the temperature was raised to 75℃, 8g of pentaerythritol and 2g of dibutyltin dilaurate were added for cross-linking reaction, and after reacting for 2h, the mixture was filtered, washed, dried and ground in sequence to obtain PUR coated talcum powder masterbatch.
[0073] Example 3
[0074] Example 3 provides a PUR protective hose, the raw materials including: 60kg of PUR resin, 10kg of SBS elastomer, 8kg of maleic anhydride grafted SBS copolymer, 3kg of itaconic acid grafted SBS copolymer, 8kg of PUR coated talc masterbatch, 2kg of calcium stearate and 0.8kg of antioxidant; wherein the antioxidant is a compound antioxidant of 1076 and 1010 type antioxidants in a mass ratio of 1:1.
[0075] Example 3 provides a method for preparing a PUR protective hose, comprising the following steps: mixing the raw materials uniformly by weight and then extruding the raw materials into a tube to obtain the PUR protective hose.
[0076] Example 3 also provides a method for preparing a maleic anhydride grafted SBS copolymer, comprising the following steps:
[0077] SBS and xylene were placed in a four-necked flask and heated to 105°C. After SBS was completely dissolved, the grafted monomer MAH and the initiator BPO were added, and nitrogen was introduced for protection. The reaction was carried out at 105°C for 4 hours. Then, anhydrous ethanol as a precipitant was added to the system while stirring at a high speed. The product was separated by vacuum filtration and repeatedly washed with a precipitant. Finally, it was vacuum dried at 90°C to obtain a maleic anhydride grafted SBS copolymer.
[0078] Example 3 also provides a method for preparing an itaconic acid grafted SBS copolymer, comprising the following steps:
[0079] SBS and xylene were placed in a four-necked flask and heated to 105°C. After SBS was completely dissolved, the grafting monomer ITA and initiator BPO dissolved in n-butanol were added, nitrogen was introduced for protection, and the reaction was carried out at 105°C for 4 hours. Then, the precipitant acetone was added to the system while stirring at a high speed. The product was separated by vacuum filtration and repeatedly washed with the precipitant. Finally, it was vacuum dried at 90°C to obtain the itaconic acid grafted SBS copolymer.
[0080] Embodiment 3 also provides a method for preparing a PUR-coated talc masterbatch, comprising the following steps:
[0081] 1000g of talc was dried in an oven at 100℃ for 6h, placed in a 5L four-necked flask, 30g of MDI and 2000mL of xylene were added, nitrogen was introduced to remove the air in the flask, the temperature was raised to 40℃, ultrasonic dispersion was performed for 30min while stirring fully, and then a mixed solution of 70g of polyether polyol N220 and 100mL of xylene was added dropwise to the three-necked flask, and the addition was completed within half an hour. Then the temperature was raised to 75℃, 8g of pentaerythritol and 2g of dibutyltin dilaurate were added for cross-linking reaction, and after reacting for 2h, the mixture was filtered, washed, dried and ground in sequence to obtain PUR coated talc masterbatch.
[0082] Example 4
[0083] The difference between the PUR protective hose provided in Example 4 and Example 3 is that the raw materials further include: 15 kg of ADP and 1 kg of masterbatch.
[0084] The preparation method of the PUR protective hose, maleic anhydride grafted SBS copolymer, itaconic acid grafted SBS copolymer, and PUR coated talc masterbatch provided in Example 4 is the same as that in Example 3.
[0085] Example 5
[0086] The difference between the PUR protective hose provided in Example 5 and Example 3 is that the raw materials further include: 20 kg of ADP and 5 kg of masterbatch.
[0087] The preparation method of the PUR protective hose, maleic anhydride grafted SBS copolymer, itaconic acid grafted SBS copolymer, and PUR coated talc masterbatch provided in Example 5 is the same as that in Example 3.
[0088] Comparative Example
[0089] Comparative Example 1
[0090] Comparative Example 1 provides a PUR protective hose, which is different from Example 5 in that the itaconic acid grafted SBS copolymer is replaced by the maleic anhydride grafted SBS copolymer in equal amounts, as follows:
[0091] Comparative Example 1 provides a PUR protective hose, the raw materials including: 60kg of PUR resin, 10kg of SBS elastomer, 12kg of maleic anhydride grafted SBS copolymer, 8kg of PUR coated talc masterbatch, 2kg of calcium stearate and 0.8kg of antioxidant; wherein the antioxidant is a compound antioxidant of 1076 and 1010 type antioxidants in a mass ratio of 1:1.
[0092] The preparation method of the PUR protective hose, maleic anhydride grafted SBS copolymer, and PUR coated talc masterbatch provided in Comparative Example 1 is the same as that in Example 5.
[0093] Comparative Example 2
[0094] Comparative Example 2 provides a PUR protective hose which is different from Example 5 in that the maleic anhydride grafted SBS copolymer is replaced by an itaconic acid grafted SBS copolymer in equal amounts, as follows:
[0095] Comparative Example 2 provides a PUR protective hose, the raw materials including: 60kg of PUR resin, 10kg of SBS elastomer, 12kg of itaconic acid grafted SBS copolymer, 8kg of PUR coated talc masterbatch, 2kg of calcium stearate and 0.8kg of antioxidant; wherein the antioxidant is a compound antioxidant of 1076 and 1010 type antioxidants in a mass ratio of 1:1.
[0096] The preparation method of the PUR protective hose, maleic anhydride grafted SBS copolymer, itaconic acid grafted SBS copolymer, and PUR coated talc masterbatch provided in Comparative Example 2 is the same as that in Example 5.
[0097] Comparative Example 3
[0098] Comparative Example 3 provides a PUR protective hose which is different from Example 5 in that the maleic anhydride grafted SBS copolymer and the itaconic acid grafted SBS copolymer are replaced by SBS in equal amounts, as follows:
[0099] Comparative Example 3 provides a PUR protective hose, the raw materials of which include: 60 kg of PUR resin, 30 kg of SBS elastomer, 2 kg of calcium stearate and 0.8 kg of antioxidant; wherein the antioxidant is a compound antioxidant of 1076 and 1010 type antioxidants in a mass ratio of 1:1.
[0100] The preparation method of the PUR protective hose and PUR coated talc masterbatch provided in Comparative Example 3 is the same as that in Example 5.
[0101] Comparative Example 4
[0102] Comparative Example 4 provides a PUR protective hose which is different from Example 5 in that the maleic anhydride grafted SBS copolymer, itaconic acid grafted SBS copolymer, and SBS are replaced with PUR resin in equal amounts, as follows:
[0103] Comparative Example 4 provides a PUR protective hose, the raw materials of which include: 90 kg of PUR resin, 2 kg of calcium stearate and 0.8 kg of antioxidant; wherein the antioxidant is a compound antioxidant of type 1076 and type 1010 antioxidants in a mass ratio of 1:1.
[0104] The preparation method of the PUR protective hose and PUR coated talc masterbatch provided in Comparative Example 4 is the same as that in Example 5.
[0105] Comparative Example 5
[0106] Comparative Example 5 provides a PUR protective hose which differs from Example 5 in that an equal amount of PUR coated talcum powder masterbatch is replaced with talcum powder.
[0107] The preparation method of the PUR protective hose, maleic anhydride grafted SBS copolymer, and itaconic acid grafted SBS copolymer provided in Comparative Example 5 is the same as that of Example 5.
[0108] Comparative Example 6
[0109] Comparative Example 6 provides a PUR protective hose which is different from Example 5 in that an equal amount of PUR coated talc masterbatch is replaced by modified talc.
[0110] Comparative Example 6 provides a method for modifying talcum powder, which specifically comprises the following steps:
[0111] Prepare a solution of silane coupling agent KH-570, stir it evenly, then drop it into the dried talcum powder, stir it for 60 minutes to allow the treatment agent to fully cover the filler, and then heat and dry it to obtain the modified talcum powder.
[0112] Comparative Example 6 provides a PUR protective hose, a maleic anhydride grafted SBS copolymer, and an itaconic acid grafted SBS copolymer, the preparation method of which is the same as that of Example 5.
[0113] Performance Testing
[0114] The PUR protective hoses provided in Examples 1-5 and Comparative Examples 1-6 were tested for mechanical properties and abrasion resistance. The specific test methods are as follows:
[0115] Refer to the requirements of Section 6.3.3 of MBN_LV_312-3_2017-09, use the finished product test, and perform the following method conditions: Test conditions: sample length: 100mm; test rate: 100mm / min; fixture distance: 50mm; observe the surface of the extruded tube of each formula and record whether the frosting is good or not.
[0116] Wear resistance test is in accordance with ISO 6722-1:2011 Section 5.12.4.2. Product pretreatment conditions: 23℃±5℃, 45~75%RH, 16h; Test conditions: Test frequency: (55±5) cycles / min; Test load: 7N, Grinding needle diameter: 0.45mm±0.01mm; Wear length: 20mm±1mm; Grinding needle length: 15.5mm±1mm; Grinding needle replacement frequency: 1 time / pcs; Mandrel specification: Φ9mm.
[0117] The test results of the mechanical properties and wear resistance of the PUR protective hoses provided in Examples 1-5 and Comparative Examples 1-6 are shown in Table 1.
[0118] Table 1 Mechanical properties and wear resistance of PUR protective hoses provided in Examples 1-5 and Comparative Examples 1-6
[0119]
[0120] The data in Table 1 reflect the significant differences in mechanical properties and wear resistance between Examples 1-5 and Comparative Examples 1-6. The tensile force and elongation of the examples are better than those of the comparative examples, and the wear resistance is also greatly improved. The tensile force of Examples 1 to 5 ranges from 425N to 439N, and the elongation is between 279% and 292%, while the tensile force of the comparative examples is concentrated between 320N and 393N, and the elongation ranges from 130% to 164%. This difference shows that the example hose using modified materials and optimized formulas has better mechanical properties and can withstand greater tensile stress and higher deformation capacity.
[0121] In terms of wear resistance, the wear times of Examples 1-5 increased from 45691 times (Example 1) to the highest 56004 times (Example 3), while the wear resistance of the comparative example was significantly lower, with the highest being only 35809 times (Comparative Example 2). This result is due to the use of PUR-coated inorganic fillers and graft-modified SBS elastomers in the examples. These modified materials not only enhance the wear resistance of the hose, but also form a frosted texture with friction on its surface, further reducing the slippage problem caused by the smooth surface during use.
[0122] The surface effect is a direct reflection of the frosted texture and the smooth surface. The surfaces of Examples 1 to 5 are all frosted, while the surface effects of Comparative Examples 1 to 6 are smooth. This shows that the examples achieve a uniform frosted effect on the hose surface through improvements in material design and processing technology, thereby providing higher friction during installation and being suitable for complex working environments.
[0123] Surface roughness test
[0124] The PUR protective hoses provided in Examples 1-5 and Comparative Examples 1-6 were subjected to a surface roughness test, and the specific test method and conditions were as follows:
[0125] (1) Contact measurement method
[0126] Instrument: Stylus surface roughness tester (such as Taylor Hobson, Mitutoyo, etc.).
[0127] step:
[0128] Prepare the sample: Clean the surface to remove oil and dust.
[0129] Calibrate the instrument: Use a standard block to calibrate the roughness tester to ensure accurate measurement of the instrument.
[0130] Set parameters: enter the measuring length, sampling length (such as 0.8mm) and evaluation length (such as 4mm).
[0131] Scanning surface: The stylus moves at a constant speed (e.g. 0.5 mm / s) to collect surface height data.
[0132] Calculation results: The instrument's built-in algorithm calculates roughness parameters such as Ra, Rz, and Rq based on the collected data.
[0133] (2) Non-contact measurement method
[0134] Instrument: Laser interferometer, white light interferometer or confocal microscope.
[0135] step:
[0136] Optical system calibration: adjust the instrument optical path and focus.
[0137] Sample installation: Place the surface to be measured on the instrument sample stage to ensure stability.
[0138] Measuring surfaces: Scanning surfaces with laser or white light to collect height data.
[0139] Analyze the data: Use software to generate 3D surface profiles and calculate roughness parameters.
[0140] Test Parameters
[0141] The following key parameters usually need to be set when testing surface roughness:
[0142] Sampling length: the length of a single segment of data sampling, typical values are 0.08mm, 0.25mm, 0.8mm, etc.
[0143] Evaluation length: The total measuring length including multiple sampling lengths, usually 4 or 5 times the sampling length.
[0144] Stylus radius (contact type): The radius of the stylus tip, generally 2μm or 5μm.
[0145] Measuring speed: stylus or optical scanning speed, typical value is 0.5mm / s.
[0146] The surface roughness data of the PUR protective hoses provided by Examples 1-5 and Comparative Examples 1-6 are shown in Table 2 below.
[0147] Table 2 Surface roughness of the PUR protective hose provided by Examples 1-5 and Comparative Examples 1-6
[0148]
[0149] The data in Table 2 show the difference in surface roughness between Examples 1-5 and Comparative Examples 1-6, which directly reflects the difference in the surface texture of the hose. The Ra values of Examples 1 to 5 are between 1.0 and 1.2 μm, and the Rz values are between 6.0 and 6.5 μm, indicating that their surfaces have a uniform frosted texture. This moderate roughness can enhance the friction performance of the hose and prevent slippage, while maintaining a good touch and aesthetic appearance.
[0150] The surface roughness of Comparative Examples 1 to 6 is significantly lower, with Ra values concentrated between 0.3 and 0.5 μm and Rz values of only 1.5 to 2.2 μm, indicating that the surfaces are smooth. Although such surfaces may reduce the resistance of the material in some cases, the smooth surface easily causes the hose to slip during installation and use, which is not conducive to the use requirements under complex working conditions.
[0151] The frosted surface effect of the embodiment is due to the introduction of PUR-coated inorganic fillers and graft-modified SBS elastomers. These modified materials form a stable and uniform frosted layer on the hose surface by optimizing particle dispersibility and interface compatibility. At the same time, the reasonable addition of flame retardants and lubricants in the formula further enhances the surface performance, ensuring the frosted texture while avoiding processing and use problems caused by excessive roughness.
[0152] For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived from them are still within the scope of protection of the claims of the invention.
Claims
1. A PUR protective hose, characterized in that: The raw materials, measured in parts by weight, include: 40-80 parts of PUR resin, 5-15 parts of SBS elastomer, 5-10 parts of maleic anhydride grafted SBS copolymer, 1-5 parts of itaconic acid grafted SBS copolymer, 5-10 parts of PUR coated inorganic filler masterbatch, 1-3 parts of lubricant and 0.5-1 part of antioxidant.
2. A PUR protective hose according to claim 1, characterized in that: The PUR resin includes one or more of polyester resin and polyether resin; the hardness of the PUR resin is 75A to 90A; The inorganic filler includes one or more of white carbon black, glass fiber, light calcium carbonate, heavy calcium carbonate, talc, mica, kaolin, silicon dioxide, titanium dioxide, red mud, fly ash, diatomaceous earth, wollastonite, glass microspheres, barium sulfate and calcium sulfate; The lubricant includes one or more of paraffin, polyethylene wax, stearic acid, hydroxystearic acid, vinyl bisstearamide, butyl stearate, oleamide, barium stearate, zinc stearate, calcium stearate, cadmium stearate, magnesium stearate, lead stearate, and silicone oil; The antioxidant includes one or more of a hindered phenol antioxidant, a phosphite antioxidant and a hindered amine antioxidant.
3. A PUR protective hose according to claim 1, characterized in that: The raw materials also include 15 to 20 parts of flame retardant and 1 to 5 parts of masterbatch in parts by weight.
4. A PUR protective hose according to claim 3, characterized in that: The flame retardant includes one or more of halogen flame retardant, phosphorus flame retardant, nitrogen flame retardant, phosphorus nitrogen flame retardant and inorganic hydroxide; the masterbatch includes masterbatch with PUR carrier.
5. A method for preparing a PUR protective hose as claimed in any one of claims 3 to 4, characterized in that: The method comprises the following steps: uniformly mixing PUR resin, SBS elastomer, maleic anhydride grafted SBS copolymer, itaconic acid grafted SBS copolymer, PUR coated inorganic filler masterbatch, lubricant, antioxidant, flame retardant and masterbatch raw materials according to weight proportions, and then extruding and forming the mixture to obtain the PUR protective hose.
6. The method for preparing a PUR protective hose according to claim 5, characterized in that: Preparation method of the maleic anhydride grafted SBS copolymer The method comprises the following steps: dissolving an SBS elastomer in an organic solvent and copolymerizing the SBS elastomer with a maleic anhydride monomer under the action of an initiator, and performing precipitation and filtering to obtain the maleic anhydride grafted SBS copolymer.
7. The method for preparing a PUR protective hose according to claim 6, characterized in that: The preparation method of the maleic anhydride grafted SBS copolymer comprises the following steps: The SBS elastomer is dissolved in xylene, maleic anhydride monomer and initiator BPO are added, and the temperature is raised to 100° C. to 110° C. in an inert atmosphere for reaction for 3 h to 5 h, and anhydrous ethanol is added for precipitation, filtered, washed, and dried to obtain the maleic anhydride grafted SBS copolymer.
8. The method for preparing a PUR protective hose according to claim 5, characterized in that: Preparation method of itaconic acid grafted SBS copolymer The method comprises the following steps: dissolving an SBS elastomer in an organic solvent and copolymerizing itaconic acid monomer under the action of an initiator, and performing precipitation and filtering to obtain the maleic anhydride grafted SBS copolymer.
9. The method for preparing a PUR protective hose according to claim 8, characterized in that: The preparation method of the itaconic acid grafted SBS copolymer, The process includes: The SBS elastomer is dissolved in xylene, and itaconic acid monomer and initiator BPO are added. In an inert atmosphere, the temperature is raised to 100° C. to 110° C. for reaction for 3 h to 5 h. Acetone is added for precipitation, and the mixture is filtered, washed, and dried to obtain the itaconic acid grafted SBS copolymer.
10. The method for preparing a PUR protective hose according to claim 5, characterized in that: The PUR coated inorganic filler masterbatch is prepared by dispersing an inorganic filler and an isocyanate in an organic solvent, dropping a polyether polyol solution, adding a crosslinking agent after heating, and performing a crosslinking reaction under the action of a catalyst; The preparation method of the PUR coated inorganic filler masterbatch, The process includes: The inorganic filler and isocyanate MDI are dissolved in xylene and fully dispersed under an inert atmosphere, and then a mixed solution of polyether polyol and xylene is added dropwise, the temperature is raised to 70° C. to 80° C., and a crosslinking agent pentaerythritol and a catalyst dibutyltin dilaurate are added to carry out a crosslinking reaction for 2 h to 2.5 h. After filtering, washing, drying and grinding, the PUR-coated inorganic filler masterbatch is obtained.
Citation Information
Patent Citations
Natural fiber reinforcement halogen-free flame retardant polypropylene composite material and preparation method thereof
CN101418099A
High-elasticity halogen-free flame-retardant frosted matte TPU electric wire sheath material and preparation method thereof
CN106497017A
Thermoplastic polyurethane composition and preparation method thereof
CN106609033A
Low-density, high-wear-resistance and high-skid-resistance TPU for shoe outsole and preparation method thereof
CN110982248A
Flame retardant for polyurethane material as well as preparation method and application thereof
CN111234317A